Concepts in world politics - Berenskoetter, Felix (Los Angeles : Sage, 2016)
Recognizing the vital importance of concepts in shaping our understanding of international relations, this ground-breaking new book puts concepts front and centre, systematically unpacking them in a clear, critical and engaging way. With contributions from some of the foremost authorities in the field, Concepts in World Politics explores 17 core concepts, from democracy to globalization, sovereignty to revolution, and covers:. The multiple meanings of a concept, where these meanings come from, and how they are employed theoretically and practically. The consequences of using concepts to frame the world in one way or another. The method of concept analysis A challenging and stimulating read, Concepts in World Politics is an indispensable guide for all students of international relations looking to develop a more nuanced and sophisticated ...
chapter 1. Unpacking concepts -- chapter 2. Power -- chapter 3. Security -- chapter 4. Rationality -- chapter 5. Identity -- chapter 6. War -- chapter 7. Peace -- chapter 8. Anarchy -- chapter 9. Society -- chapter 10. Capitalism -- chapter 11. Sovereignty -- chapter 12. Hegemony -- chapter 13. Democracy -- chapter 14. Religion -- chapter 15. Revolution -- chapter 16. Intervention -- chapter 17. Integration -- chapter 18. Globalization.
Includes bibliographies and index.
Description based on MARC record for print version.
Keywords: International relations